Factors associated with statin-related adverse muscular events in adult dyslipidemic outpatients - Paula Ferreira Castro; Eliane Ribeiro; Egidio Lima Dorea; Gelba Almeida Pinto; Rosario Dominguez Crespo Hirata (Universidade de São Paulo, 2018)
ABSTRACT Statins are the most prescribed lowering-cholesterol drugs. They are well tolerated, however, some patients present muscular adverse symptoms. Clinical and laboratory data from 120 dyslipidemic patients prescribed with statins were obtained from January to December/2013 at a University Hospital in Sao Paulo city, Brazil, to study factors associated with statin-related adverse muscular events (AME). Pharmacotherapy and statin-related AME data (serum CK elevation and any degree of myopathy, myalgia, myositis or rhabdomyolysis) of the dyslipidemic patients were recorded. The study was approved by local Ethics Committees. Simvastatin (70%) and atorvastatin (25%) were the most prescribed statins. AME related to statin treatment were found in 17% of the patients. Mean age and use of simvastatin were lower in AME group than non-AME group (p<0.05). Simvastatin users were less likely to develop AME than atorvastatin users (OR=0.21; 95%CI=0.07-0.57; p<0.01). The use of P-glycoprotein (ABCB1) efflux pump inhibitors was associated with high risk for AME (OR=5.26; 95%CI=1.55-17.79; p<0.01). Serum liver enzymes were increased up to three-fold in 2.5% of the statin-treated patients. The results are suggestive that the type of statin prescribed and the concomitant use of ABCB1 inhibitors increase the susceptibility to adverse muscular events during statin therapy in dyslipidemic outpatients.